Biostimulants of semidesert plants in the root and aerial growth of tomato seedlings - Jasso-de Rodríguez, Diana; Ramírez-Pérez , Carmen; Ramírez-Rodríguez , Homero; Villarreal-Quintanilla, José Ángel; Hernández-Pérez, Armando; Díaz-Jimenez, M. Lourdes Virginia; Peña-Ramos, Fidel M. (Ecosistemas y Recursos Agropecuarios, 2024)
Biostimulants are a new sustainable alternative to promote the growth and development of vigorous seedlings in the greenhouse. In the present research, the objective was to evaluate extracts from three semi-desert plants as biostimulants, in the root and aerial growth of seedlings of two varieties of tomato, saladette (Río Grande) and ball (Beef Bang F1), in vitro evaluations were carried out and under greenhouse. The in vitro evaluation was done with the purpose of selecting the extracts that would be used in the greenhouse stage. In vitro, plant extracts from: Rhus muelleri (RM), R. virens (RV), Jatropha dioica (JD) and Juglans mollis(JM) were evaluated at three concentrations each, 75, 100 and 200 mg L-1 and two commercial controls: rooters Rootex (RT) and Raizal (RZ) and an absolute control, without extract or rooters (TC). The total length of the radicle and plumule and the fresh weight of the seedling were evaluated. In the greenhouse, it was first evaluated in a seedbed and then in a pot, the extracts were: RV, RM, JD and RJ, in concentrations of 75 and 200 mg L-1 and the same controls. In both stages, diameter and length of root and stem, fresh and dry weight of root and stem, were evaluated. The extracts of RM 200 and JD 75 had greater stimulation than the commercial rooters, in the root and aerial growth of the seedlings of the two tomato varieties, in vitro, in seedbed and in pots, after transplanting.